Plithogenic Hypersoft based Plithogenic Cognitive Maps in Sustainable Industrial Development - N. Angel; P. Pandiammal; Nivetha Martin (Neutrosophic Sets and Systems)
Plithogenic Cognitive Maps (PCM) is a comprehensive decision tool discussed in diverse dimensions. The development of PCM models is indispensable in the domain of decision-making. This research work proposes theoretical framework of Plithogenic hypersoft sets (PHS) based PCM. This is a novel approach to make optimal decisions by considering several aspects simultaneously. The objective of this integrated approach is to make concurrent investigations on the interassociational impacts between the factors of the problem taken into account. The PHS based PCM is applied to a decision - making scenario of sustainable industrial development to demonstrate the significance of this PHS based PCM. The future directions and extensions of this work are also presented in this paper.